2018
DOI: 10.1038/s41417-017-0005-y
|View full text |Cite|
|
Sign up to set email alerts
|

miR-200c inhibits TGF-β-induced-EMT to restore trastuzumab sensitivity by targeting ZEB1 and ZEB2 in gastric cancer

Abstract: Gastric cancer is the fifth most common malignancy in the world, with Eastern Asia as one of areas with the highest incidence rates. Trastuzumab, a HER2-targeting antibody, combined with chemotherapy has been successfully employed for the gastric cancer patients with HER2 overexpression/amplification. However, trastuzumab resistance is a major problem in clinical practice. Here we observed that the trastuzumab-resistant gastric cancer cell line NCI-N87/TR expressed high levels of epithelial-mesenchymal transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 31 publications
3
49
0
Order By: Relevance
“…We confirmed the activatory role of miR-145, miR-200c, miR-205 on CDH1 expression in VRCs. We also confirmed that miR-200c expression decreased ZEB1 level in VRCs [53], but we did not observe any effect on miR-200c on ZEB2 expression [54]. VRCs overexpressed miR-205 shown ZEB1/2 downregulation in cancer cells, what is in accordance with previous works [55,56].…”
Section: Discussionsupporting
confidence: 92%
“…We confirmed the activatory role of miR-145, miR-200c, miR-205 on CDH1 expression in VRCs. We also confirmed that miR-200c expression decreased ZEB1 level in VRCs [53], but we did not observe any effect on miR-200c on ZEB2 expression [54]. VRCs overexpressed miR-205 shown ZEB1/2 downregulation in cancer cells, what is in accordance with previous works [55,56].…”
Section: Discussionsupporting
confidence: 92%
“…It was demonstrated that miR-200c is down-regulated in TGF-β-treated or trastuzumab-resistant gastric cancer cells and targets ZEB1 and ZEB2. Therefore, over-expression of miR-200c can reverse trastuzumab resistance in gastric cancer cells [164]. Moreover, the over-expression of miR-200 family (miR-200a, miR-200b, and miR-429) was found to block the EMT process, thereby reversing therapeutic resistance, rather than impacting lung metastasis in an orthotopic breast tumor model [163] (Table 5).…”
Section: Mirnas Directly Regulating Emt-related Transcription Factorsmentioning
confidence: 99%
“…Gastric cancer (GC) is the fourth most common cancer and the second leading cause of cancer-associated mortality worldwide (1). The incidence and mortality rates of GC are the highest in East Asia, primarily in China (1)(2)(3). Gastric carcinogenesis is a complex process, which involves crosstalk among host, environmental and bacterial factors, leading to different molecular alterations at the genetic and epigenetic level; Helicobacter pylori is a well-recognized high-risk factor (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy resistance frequently emerges as a cause of treatment failure (6). At present, the outcome for patients with advanced GC remains poor, with 5-20% 5-year survival and a median overall survival of 10 months (3). Therefore, examining novel biomarkers for early diagnosis and other feasible treatments based on a better understanding of mechanisms underlying GC pathogenesis, in addition to chemoresistance, is urgently required.…”
Section: Introductionmentioning
confidence: 99%